2015
DOI: 10.1002/jbm.a.35465
|View full text |Cite
|
Sign up to set email alerts
|

Coculture of dorsal root ganglion neurons and differentiated human corneal stromal stem cells on silk-based scaffolds

Abstract: Corneal tissue displays the highest peripheral nerve density in the human body. Engineering of biomaterials to promote interactions between neurons and corneal tissue could provide tissue models for nerve/cornea development, platforms for drug screening, as well as innovative opportunities to regenerate cornea tissue. The focus of this study was to develop a co-culture system for differentiated human corneal stromal stem cells (dhCSSCs) and dorsal root ganglion neurons (DRG) to mimic the human cornea tissue in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…5 b), the OD values of cells cultured using a Transwell insert and with the electrospun PLLA MTAM revealed a significantly higher OD value, which indicates the importance of coculture and "supporting cells" in the regeneration of nerves. Similar observations have been made by several other groups, confirming the superior cell viability of cells cultured in a coculture setting versus cells cultured in a monoculture setting [Liu et al, 2013;Wang et al, 2015]. Overall the MTT data demonstrated that combination of the 3-D structure of the electrospun PLLA MTAM with an ultrathin lumen wall ( Fig.…”
Section: Discussionsupporting
confidence: 74%
“…5 b), the OD values of cells cultured using a Transwell insert and with the electrospun PLLA MTAM revealed a significantly higher OD value, which indicates the importance of coculture and "supporting cells" in the regeneration of nerves. Similar observations have been made by several other groups, confirming the superior cell viability of cells cultured in a coculture setting versus cells cultured in a monoculture setting [Liu et al, 2013;Wang et al, 2015]. Overall the MTT data demonstrated that combination of the 3-D structure of the electrospun PLLA MTAM with an ultrathin lumen wall ( Fig.…”
Section: Discussionsupporting
confidence: 74%
“…Current corneal tissue in vitro models mainly focus on corneal epithelial and stromal cells and use collagen as substrates [14, 15]. Among the few co-culture studies that used corneal cells and neurons [15, 16], layers of collagen hydrogel were used to resemble the lamellar structure of cornea but failed to recapitulate the alignment of the stromal cells and the multi-layer features of the epithelial cells. Further, the native density of nerve endings and branches has also not been achieved through in vitro cultures.…”
Section: Introductionmentioning
confidence: 99%
“…The silk can also be formed into sponges which can support neuron growth and the formation of neuronal connections [24–26]. In our previous study [16], 2D human corneal stromal stem cells (hCSSCs) and dorsal root ganglion neurons (DRG) in a co-culture system was generated and we observed that axon length increased when the DRGs were co-cultured with the hCSSCs.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, samples grown in αMEM + 16.5% FBS (standard medium) were used as control for nonexogenously stimulated cells. DMEM/F-12 is a complex medium widely used for culturing neuronal cells [26,27] and inducing neuronal differentiation of neural precursors or stem cells when supplemented with either specific growth factors [28][29][30] or RA [31][32][33].…”
Section: Hcmcs Neuronal Differentiationmentioning
confidence: 99%